Latest Advances and New Visions of Ontology in Information Science - SaberiKamarposhti, Morteza; Sahlabadi, Mahdi (IntechOpen, 2023)
Ontology is a formal characteristic and an entity of perception and concept. The characteristic of an ontology is the formal description of a set of terms and the relationships between them, which is obtained with a special language and in a file that can be understood by computers. Ontologies could be employed in several domains, such as global semantic networks, search engines, electronic commerce, natural language processing, knowledge engineering, information extraction and retrieval, multi-agent systems, qualitative modeling of physical systems, database design, information systems, and geographic and digital libraries. This book presents the latest advances and new visions in the field of ontology in information science.